Prevalence of Work Musculoskeletal Disorder in Patients Handling Tasks Among Nursing Staff in Critical Care-Unit - Mebarki, Bouhafs; Zaoui, Brahim; Mokdad, Mohamed; Mebarki, Imed Eddine (Spektrum Industri, 2023)
Awkward postures imposed by nursing duties are a main source of work-related musculoskeletal disorders among nursing staff. The purpose of this article is to describe the prevalence of work-related musculoskeletal disorders among critical care nurses, in two patient handling tasks, transferring and repositioning of patients, and assess their training level and acquaintance of ergonomics rules and principles in patients’ handling tasks. Results of the study revealed a large number of nurses in intensive care unit exhibit musculoskeletal disorders symptoms. Nurses knowledge of safe patients handling technics are superficial and lacking basic human factors /ergonomics principles. The study recommended the immediate hiring of an adequate number of physically able nursing staff and providing the necessary work equipment to assist nurses perform patient handling tasks. In the near future, a human factors/ergonomics intervention program should be launched, incorporating a "Safe Patient Handling Training Program” for the critical care-unit staff